Criteria of probabilities theory in contingencies assessment in the peruvian mining companies - Castañeda Moreano, Rosa Milagros (2020)
Objective: Comprehend the definitions and properties of the Probability Theory in order to consider in the evaluation of financial information on contingencies, emphasizing the probability concept. Method: The research is a qualitative approach, of exploratory type and partially descriptive, of non-experimental and cross-sectional design, with hypothetical assumptions, based on the information analysis, case studies and semi structured interviews. Results: Contingencies are revealed in notes rather than being recognized in the financial statements. The level of revelation is not enough in terms of judgments applied in the estimates, as well as in their impracticability and rationality. Conclusions: The concept of probability in international financial reporting standards differs from the concept stablished in the Probabilities Theory. The probabilities estimation should consider the nature and characteristics of the contingency and the probability of the event occurrence, translated into winning or losing a dispute, considering the Bayesian approach, since it measures the belief about the occurrence of an event.